Flemish maritime ports, Liège port complex and the port of Brussels – Report 2015 - Claude Mathys (National Bank of Belgium, 2017)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centers facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2010-2015, with an emphasis on 2015. Focusing on the three major variables of value added, employment and investment, the report also provides some information based on the social balance sheet and an overview of the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. As a result of the underlying calculation method the changes of indirect employment and indirect value added can differ from one another. The developments concerning economic activity in the six ports in 2014-2015 are summarized in the table on the next page. In 2015 the growth of maritime traffic in the Flemish maritime ports was due to developments in the port of Antwerp and the port of Ghent. Direct value added increased in all Flemish maritime ports in 2015. However, direct employment is continuing to decline. Investment was down everywhere except in the port of Zeebrugge. Cargo traffic in the Liège port complex declined in 2015, whereas it slightly slowed down in the port of Brussels. At the same time, direct value added in Liège shrank while it rose sharply in the port of Brussels. By contrast, direct employment was down in both ports. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2015.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport; intermodality; public investments